The innovative use of social media for teaching English as a second language - Rwodzi, Christopher; de Jager, Lizette; Mpofu, Nhlanhla (Journal for Transdisciplinary Research in Southern Africa, 2020)
The need to improve English proficiency and inclusion of social media in language teaching have resulted in teachers having to develop new teaching strategies incorporating digital tools. In South Africa, English teachers in township settings have to develop teaching strategies suitable for teaching English using social media platforms, especially in resource-constrained secondary schools. From literature and education policies, teaching of digital literacy is strongly recommended, but teachers in some township environments are not pedagogically capacitated to teach and use social media in teaching English. To explore the experiences of such teachers, this study explored the use of social media for the teaching of English as a second language in township schools. The study used an interpretivist qualitative approach in an exploratory case-study design to understand teachers' initiatives and strategies in teaching English as a second language using social media. Data collection was done using semi-structured interviews with open-ended questions and document analysis. Teachers' voices, actions and documents on the use of social media were analysed inductively and thematically. The research findings indicate that the sampled English teachers used social media for collaboration, networking, communication and out-of-school digital literacy practices as their initiatives. These digital initiatives lead to the utilisation of digital connection platforms for socialisation and teaching and learning English. In addition to dividends of connectivism, visual communication and cyber linguistics were found to have become critically important practices for learners learning English as a second language. The implication is that the education policy-makers and planners in South Africa need to revisit the policy on e-learning and Information Communication Technology (ICT) usage in schools to incorporate the methodological requirements and competences for teachers to use in the teaching of English using social media. In addition to improvements in policy measures, English teachers in resource-constrained township secondary schools need to improve their digital literacy skills to line up themselves for online and out-of-school literacy learning requirements.